An Assessment of the Absorptive Capacity of Agencies Involved in the Public Works Sector - Rosario G. Manasan; Ruben G. Mercado (Philippine Institute for Development Studies (PIDS), 2001)
This study evaluates the absorptive capacity of a government agency for domestic and external funds. It takes the case of the Department of Public Works and Highways (DPWH), one of the biggest recipients of funds from government and foreign sources. Specifically, the paper a) provides an assessment of the institutional framework, capability and absorptive capacity of the DPWH to implement local and foreign-funded projects and programs; b) develops measures or indicators to assess the agencys absorptive capacity with respect to available resources; c) identifies issues within the agency and with related institutions in financial management and implementation of programs/projects; and d) formulates recommendations on how to strengthen the agencys capacity to utilize resources. The study makes specific reference to the extent or magnitude of resources utilized, the particular programs where low utilization are more prevalent and the factors that hinder the full absorption of available money that are within and beyond the agencys control. The paper lists down some concrete recommendations for the agency and its partner institutions that will help improve its overall capacity for fund absorption.
Keywords: 330; governance; absorptive capacity; public works; public finance; Local Government Units (LGUs)